Links between academic motivation, psychological need satisfaction in education, and university students' satisfaction with their study - Puklek Levpušček, Melita (Array, 2019)
Student motivation represents an important factor in their academic performance. The present study explored university students' academic motivation across the academic year and its relationship with psychological need satisfaction in the study context and academic adjustment. Deci and Ryan's Self-Determination Theory (SDT) presents a theoretical framework of this study. 124 students participated in both waves of data collection. They answered the Academic Motivation Scale, College Version (AMS-C 28) in the fall of the academic year, and seven months later they answered the question about their certainty of study choice and completed again the AMS-C 28. Additionally, they answered the items about their psychological need satisfaction (autonomy, competence, relatedness) in the current academic year and the items about their satisfaction with the study. The results showed that all forms of academic motivation (as distributed along the SDT motivational continuum) remained highly stable within one academic year. More autonomous motivational orientation related to higher perceived satisfaction of psychological needs. Furthermore, it significantly predicted students' satisfaction with the study and certainty about the study choice. When students' satisfaction of psychological needs in the current academic year was entered into the regression model, it predicted satisfaction with the study and certainty in study choice over and above the students' level of autonomous motivation. The study showed the importance of creating learning environments that respond to students' psychological study needs.